2015
DOI: 10.1007/s00167-015-3910-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arthroscopic and open Latarjet with a learning curve analysis

Abstract: Retrospective comparative analysis, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 21 publications
4
134
2
3
Order By: Relevance
“…5,11,39 The arthroscopic technique could increase these risks because of the specific difficulties in some of the surgical steps, such as the subscapularis split and graft positioning. 9 Consequences of subscapularis split had been widely studied in the context of open instability surgeries and open Latarjet. 5,[11][12][13]17,[36][37][38][39] However, outcomes of arthroscopic subscapularis split are still relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,39 The arthroscopic technique could increase these risks because of the specific difficulties in some of the surgical steps, such as the subscapularis split and graft positioning. 9 Consequences of subscapularis split had been widely studied in the context of open instability surgeries and open Latarjet. 5,[11][12][13]17,[36][37][38][39] However, outcomes of arthroscopic subscapularis split are still relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among 28 patients treated with an all-arthroscopic Latarjet and 36 patients treated with an open Latarjet procedure, Cunningham et al reported more frequent instances of inaccurate screw placement, longer operative times (146 vs 81 min, p=0.001) and higher complication rates (29% vs 11%, p=0.03) in the arthroscopic group without any significant differences in Walch-Duplay scores between arthroscopic and open groups. Moreover, a learning curve analysis demonstrated that 10 arthroscopic Latarjet procedures were needed to overcome the need for conversion to an open procedure 90. In our view, these data, coupled with reported rates of graft non-union and malposition, do not support the routine performance of the Latarjet procedure arthroscopically.…”
Section: Congruent Arc Latarjet Pearls and Avoiding Pitfallsmentioning
confidence: 74%
“…The arthroscopic Latarjet procedure has been in the literature since 2007. 17 Although a learning curve has been shown by many authors, 12,18,19 it also exists for the open Latarjet, 20 and should not be thought of as prohibitive. In fact, although these authors who studied their learning curve reduced their operative time with experience, even in their early series, they achieved reliable, safe results.…”
Section: Arthroscopic Latarjet: the Learning Curve Should Not Be Prohmentioning
confidence: 99%